Growth Response of Deli tobacco by giving Mount Sinabung volcanic ash and dose of compost - Daniel Sitorus; Jonis Ginting; Toga Simanungkalit (Universitas Sumatera Utara, 2016)
The purpose of the study was to determine the effect of Mount Sinabung volcanic ash and compost on the growth of Deli tobacco. The research was conducted at Balai Penelitian Tembakau Deli (BPTD) Sampali, Percut Sei Tuan District Deli Serdang Regency North Sumatera with the height of + 15 metres above sea level, began from July until September 2014. The research design was a randomized block design with two factors, the first factor was Mount Sinabung volcano ash (0 g, 500 g, 1000 g) and the second factor was dose of compost (0 g, 250 g, 500 g, 750 g). The parameters observed were plant height, stem diameter, number of leaf, sand leaf thickness, feet leaf I thickness, leaf area, root length at 18 up to 50 days after transplanting(DAT) and dry weight of plant. The result showed that volcanic ash and dose of compost and also both of interaction were not show any significant effect on all parameters.